Breaking the cage: Traveling, freedom, and English society in Iṃlaṇḍe Baṅgamahilā - Chatterjee, Sukla (Asien, 2014)
This article provides an analysis of Iṃlaṇḍe baṅgamahilā (“A Bengali Woman in England”), a travelogue written in the 19th century by a Bengali woman named Krishnabhabini Das (Kṛṣṇabhābinī Dās) (1864-1919). Despite being the most well-documented travelogue written at that time by an Indian woman, it was eventually forgotten until its recent rediscovery. The travelogue is a unique document authored by a woman in the colonial period in terms of its detail, exploration, and documenta¬tion of the socio-cultural aspects of English society. It is also an outstanding example of the ideas educated Bengalis had about England at that time. Moreover, the gendered perspective which this travelogue offers is a bright stroke of color on the variegated canvas of Indian/Bengali travel writing on imperial Britain. (Asien/GIGA)
Keywords: Indien; Großbritannien; Bengalen